Employee Performance Improvement through Additional Employee Income (TPP) at the Sentajo Raya District, Kuantan Singingi Regency, Riau Province - Sari, Febri Eka; Zulkarnaini, Zulkarnaini (FISIP Universitas Malikussaleh, 2021)
The Kuantan Singingi Regency Government has issued a Regent Regulation regarding Additional Employee Income (TPP). They hope that the legal product can improve the performance and discipline of the state civil apparatus. This study aims to describe the effectiveness of TPP in supporting employee performance improvement at the Sentajo Raya District office, Kuantan Singingi Regency, Riau Province. We used Mitchell's theory in carrying out the study. According to Mitchell, there are five indicators in measuring employee performance improvement, including quality of work, promptness, initiative, capability, and communication. The research method uses a qualitative approach. The results showed that the TPP positively improved the performance and discipline of employees at the Sentajo Raya District office because the TPP encouraged a clear division of labor. In addition, organizational leaders implement a system of rewards and punishments. Employees who perform well get additional income through the TPP, while employees who perform poorly get a TPP deduction or even get no additional income at all.ABSTRAKPemerintah Kabupaten Kuantan Singingi telah menerbitkan Peraturan Bupati mengenai Tambahan Penghasilan Pegawai (TPP). Produk hukum tersebut diharapkan dapat meningkatkan kinerja dan disiplin aparatur sipil negara. Penelitian ini bertujuan untuk menggambarkan efektivitas TPP dalam mendukung peningkatan kinerja pegawai di kantor Kecamatan Sentajo Raya, Kabupaten Kuantan Singingi, Provinsi Riau. Para peneliti dalam melaksanakan penelitian menggunakan teori Mitchell di mana indikator kinerja diukur dari lima aspek yang terkait dengan kualitas kerja, ketepatan waktu, inisiatif, kemampuan, dan komunikasi. Metode penelitian menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa TPP secara positif meningkatkan kinerja dan disiplin pegawai di kantor Kecamatan Sentajo Raya karena TPP mendorong pembagian kerja yang jelas. Selain itu, pimpinan organisasi menerapkan sistem imbalan dan hukuman. Pegawai yang berkinerja baik memperoleh tambahan penghasilan melalui TPP, sedangkan pegawai yang berkinerja buruk memperoleh pemotongan TPP atau bahkan sama sekali tidak memperoleh tambahan penghasilan.